Comparative Assessment of PAHs Reduction in Soil by Growing Zea mays L. Augmented with Microbial Consortia and Fertilizer: Modulation in Uptake and Antioxidant Defense Response. (14th September 2021) - Kumari, Babita; Kriti, Kriti; Sinam, Geetgovind; Singh, Gayatri; Jouhari, Nitanshi; Kumar, Navin; Gautam, Ambedkar; Mallick, Shekhar
Abstract: Polyaromatic hydrocarbons (PAHs) are found ubiquitously in the environment and are carcinogenic and recalcitrant in nature, hence their fate in crops is imperative to quantify. In present study, the role of petroleum hydrocarbon (PH) degrading microbial consortium and organic fertilizer in the translocation and accumulation of PAHs in a crop plant i.e., Zea mays var. NMH-589 was determined under experimental simulated condition using spiked soil with PAHs mixture (300 µg g −1 phenantherene, 300 µg g −1 anthracene, 200 µg g −1 pyrene, and 200 µg g −1 fluoranthene). After 32 days of treatment, removal of 49.7% of PAHs mixture (k = 0.01552 d −1, t1/2 = 44.6 d) in soil was observed due to growth of maize plant, compared to only 31% removal in non-planted soil (k = 0.0097, t1/2 = 71.456). While growing maize plant amended with organic fertilizer and microbial consortium ( Pseudomonas sp. BP10 and Penicillium oxalicum PS10), enhanced the degradation rate of PAHs in soil by 99.4% (k = 0.03107 d −1, t1/2 = 22.3 d). Maximum accumulation of total PAHs mixture in plant tissues (root, shoot, and leaves) was 99.5, 63.5, and 43.5 µg g −1, respectively without any amendment, while the accumulation was lowest i.e., 11.4 µg g −1, 1.2 µg g −1 and not detected, respectively when the soil was amended with microbes and cow-dung manure. Plants also stimulated the microbial count in soil by enhancing their CFU g −1 of soil up to 503%), while the addition of microbial consortium reduced the PAHs stress to plant concurrent with the decrease in antioxidant activities of the plant.